METHODOLOGICAL PRINCIPLES OF SECURITY-ORIENTED MANAGEMENT ANALYSIS BY HEALTHCARE INSTITUTIONS - HARBUSIUK, Valerii (Herald of Khmelnytskyi National University. Economic sciences, 2024)
In safety-oriented management of healthcare facilities, the role of information provided by the analysis of safety-oriented management of healthcare facilities is crucial.The effectiveness of analyzing safety-oriented management of healthcare facilities ensures the creation of a methodological basis for analysis and the use of its operationalized concepts in practical analytical activities.The methodological principles of security-oriented management analysis in healthcare institutions from a systemic approach consist of several interconnected elements, each representing a specific aspect of methodological principles. These elements include terminology, object and subjects, functions, types, goals, and tasks of the analysis. The elements of the methodological principles of analysis individualize the analysis in a certain logical sequence, regulate the relationships and connections between different forms, means, and methods of solving analysis tasks. Each of the elements of the methodological principles of analysis is thoroughly described, allowing their content to be fully disclosed.The formed methodological basis for the analysis of security-oriented management of healthcare institutions reflects the managerial nature of the analysis, general rules and conditions of its implementation, data collection, approaches and methods of their processing, generalization and interpretation of results, which constitute the methodological principles of the analysis. Adherence to them ensures the effectiveness of the analysis of security-oriented management of healthcare institutions, reliability, and relevance of its results.
Keywords: Security-oriented management; healthcare institution; analysis; managerial nature of analysis; methodological principles; elements